Growth management in the San Francisco Bay Area: Interdependence of theory and practice - Karina Pallagst (University of California, Institute of Urban and Regional Development (IURD), 2006)
Growth management has been part of US land use planning practice for decades, and a large number of activities has been developed and applied over time. The rather fragmented toolbox comprises traditional activities, like growth caps and urban growth boundaries, in conjunction with smart approaches such as transit oriented development and new urbanism-related design features. The emphasis of growth management research has been to highlight the different programs enacted at state and/or local levels. Because the scope of growth management requires myriad different tools, land use researchers must keep pace with emerging approaches, and this paper contributes to that discussion. The analytical aspect, however, will be elaborated through theoretical planning considerations.
Keywords: 330; Regionales Wachstum; Regionalplanung; San Francisco Bay (Region)